HgTe quantum wells with inverted band structure: quantum Hall effect and the large-scale impurity potential - Gudina, S.V.; Arapov, Y.G.; Neverov, V.N.; Podgornykh, S.M.; Popov, M.R.; Deriushkina, E.V.; Shelushinina, N.G.; Yakunin, M.V.; Mikhailov, N.N.; Dvoretsky, S.A. (Физика низких температур, 2019)
We report on the longitudinal and Hall resistivities of a HgTe quantum well with inverted energy spectrum (dQW = 20.3 nm) measured in the quantum Hall (QH) regime at magnetic fields up to 9 T and temperatures 2.9–50 K. The temperature dependence of the QH plateau–plateau transition (PPT) widths and of variable range hopping (VRH) conduction on the Hall plateaus are analyzed. The data are presented in a genuine scale form both for PPT regions and for VRH regime. Decisive role of the long-range random potential (the potential of remote ionized impurities) in the localization–delocalization processes in the QH regime for the system under study is revealed.